Microfiltración de una resina compuesta fluida utilizada como sellante versus un sellante convencional en dientes extraídos - Albán Gómez, Johanna Guadalupe (2019)
In vitro comparative study, in which the degree of marginal microfiltration of resin, used as sealant, was evaluated and compared versussealant. For this, 40 recent extracted healthy human premolars were used; these ones were divided into four groups A: aeropulidor, ameloplasty and resin; B: aeropulidor, ameloplasty and sealant; C: micromotor,ameloplasty and resin; and D: micromotor,ameloplasty and sealant. Degree all the samples were submitted to a thermocycling process which was between 4º C and 60º C during 250 cycles; then apexes were waterproofed with acrylic (Duralay) three layers of 2 mm Maybelline nail polish over the material are added, then they are submerged in an aqueous solution of 5% methylene blue for 24 hours. Afterwards the samples were cut perpendicularly in buccolingual way following the longitudinal axis; the faces were observed in a 100x zoom stereomicroscope; the tooth-material interface was evaluated in order to check the microfiltration. The statistical tests of normality of Mann Whitney and Chi-Cuadrado were carried out for the data process,this tests have a 95% (p<0, 05) reliably level. Outcomes: no microfiltration was observed in 80% and 70% of the samples from groups A and B, these had a value of (p = 0.127 and p = 0.616), whit of 80% and 50% of the samples from groups C and D (p=0,132 y p=0,063), no statistical significance for all group. To conclude with, the fluid resin (Opallis Flow) and the sealant (Helioseal F Vivadent) had the same behavior in the marginal microfiltration evaluation with the ameloplasty technique independently of the previous cleaning technique that is used. Key words: Sealants, compound fluid resin, microfiltration.